(untitled) (CIPEEX, 2025)
Electronic cigarettes (EC) are seen by many young people as a less harmful alternative to traditional cigarettes, mainly due to their attractive design and variety of flavors. However, EC use can result in vaping-induced lung injury (EVALI). The growing popularity of ECs among young people and the associated risks highlight the need for awareness of their adverse effects. This observational, descriptive, and quantitative study analyzed the prevalence of EC use among university students in exact sciences. A total of 180 students were analyzed, of whom 27 used cigarettes, 13 of which were ECs and 14 were other types. Most were male, aged between 21 and 24 years, single, white, and with a monthly income between two and five minimum wages. Civil and Mechanical Engineering had the highest prevalence of EC users, while Software Engineering had the highest number of traditional cigarette smokers. In addition, CE use showed variation in dependence, with a significant proportion in the "Medium" and "Very high" levels, suggesting a higher risk of dependence compared to conventional cigarette smokers. EC use is associated with addiction and anxiety and is more frequent in public places, although most prefer to smoke alone. All EC users used essences, highlighting the importance of flavors for the device’s popularity. Finally, EC use among engineering students is significant and raises concerns about the health and socialization of these young people.